Religious Tolerance in Ilorin Emirate: An Islamic Perspective - Daud Olalekan Abdulsalam; Ridwanullah Ahmad Abdulganiyu; Saheed Adewale Badmus (CV Media Inti Teknologi, 2026)
Background: In multiple societies, such as Nigeria, where various religious communities coexist, religious tolerance is an essential value. An exceptional example of long-lasting interfaith cooperation impacted by Islamic teachings and sociocultural fusion is the Ilorin Emirate.Objectives: The purpose of this study is to investigate the idea of religious tolerance from an Islamic viewpoint, as well as how it has historically and socially been used in the Ilorin Emirate and what that means for societal cohesion and peace.Method: This study uses a qualitative methodology with thematic, historical, and textual analysis. Both original sources, such as the Qur'an and Hadith, and secondary sources, such as academic literature and historical documents pertaining to the Ilorin Emirate, are used to gather data.Results: Justice (ʿadl), compassion (raḥmah), piety (taqwā), and wisdom (ḥikmah) are the four fundamental characteristics that shape religious tolerance in the Ilorin Emirate. Patterns of institutional integration, interfaith social interaction, and educational influence all reflect these ideas. The report also highlights important issues that jeopardize the longevity of tolerance, such as radical ideologies, political exploitation of religion, and socioeconomic disparity.Conclusion: By connecting Islamic theological ideas with their real-world implementation in a regional setting, this study adds to the body of literature and shows how religion can be a basis for long-term interfaith harmony. The results emphasize how crucial it is to improve religious leadership, education, and interfaith communication in order to preserve social harmony in plural society.